Understanding Women in Society Through Folklore in South Asia: Disseminating The Similarities With The Tamil Culture in The Region - Subirthana, M.S.; Sowjanyaa, V. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
Traditional Stories and Beliefs are an integral part of a human life. Every individual is bound to an identity in the form of ethnicity, religion, region, language, etc. These identities that a man inclines towards becomes the base for their beliefs and behaviour in the society. Folklore is the traditional stories and beliefs that are carried on orally from one generation to the next that is preserved and revered through people of a particular culture. These folklores can be told through music, drama, history, legends and myths. It is a common practice that these folklores are often told as bedtime stories for children, tales of wisdom as one grows up and used as cautious lessons when one is seeking answers. These tales become a great base for morale building in that particular society as they are viewed as not just tales but history of their ancestors. Thus, it is important to understand that folklore has a huge role to play in how a society builds its morale and how it influences the perception of an individual. The paper tries to analyse the same in an analytical and descriptive method. The paper tries to understand the relevance of folklore in the character building of women in South Asia, especially draw parallels into the similarities between Tamil Nadu in India and the Northern Province of Sri Lanka. The paper tries to explore the famous folklore of this region, Ramayana and how it has influenced the perception of women in society. The paper also analyses the future of folklore and the role it would play in the perception of a women and its advantages/disadvantages. The paper further tries to analyse the influence of folklore in law making and verdicts given under law towards women through exploring case studies.
Keywords: Folklore; Morale; Social institutions; law; policy making